Cross over to HTML5 game development : use your programming experience to create mobile games - Chishti, Zarrar (Apress, 2017)
Break into the most lucrative platform in the world by adding HTML5 game development to your current skillset. Zarrar Chishti has trained developers from a wide range of programming disciplines to cross over into HTML5 game development. Whatever your vocation, whether it be an Application Databases Systems developer or a Professional Web developer, with this book you will learn to evolve your current coding skills to become eligible for the biggest gaming platform in the world. From the first chapter you will see encouraging results immediately as you power through a challenging and fun project that has been uniquely designed and developed for this book. With the relentless backing of the giants of the industry including Apple and Google, HTML5 is rapidly becoming the leading technology for game development. Furthermore nearly every mobile device, tablet and PC system offer full support to the latest games developed in HTML5. Never before has there been such a widely accepted platform by literally every manufacturer and operating system. This in turn has convinced marketing departments to move away from traditional platforms, such as dedicated mobile apps, for the more widely accepted HTML5 format. There has never been a better time for a seasoned IT programmer to crossover and capitalize in this lucrative market with their much sought after talents and experience. Take the skills you already have and expand your career into HTML5 development with this book.